Preoperative percutaneous oxygen saturation is a predictor of postoperative adverse events after Ebstein's anomaly reconstruction. Issue 3 (27th January 2021) - Yang, Yao; Zhang, Wei; Liu, Yang; Li, Gang; Zhang, Han; Fan, Xing; Su, Junwu; Liu, Yinglong; Fan, Xiangming
Abstract: Background: Ebstein's anomaly (EA) is a kind of congenital heart disease, which is currently widely treated by cone reconstruction. However, the prediction of postoperative recovery is still challenging. Methods: A retrospective analysis was performed on EA cases undergoing cone reconstruction from January 2010 to January 2016. Univariate and multivariate logistic regression analyses were performed, with postoperative adverse events defined as dependent variable and pre‐ and intraoperative parameters defined as independent variables. The predictive capacity of preoperative percutaneous oxygen saturation (SPO2 ) and Great Ormond Street (GOS) score was evaluated using areas under the curve of the receiver operating characteristic (ROC). Results: Preoperative SPO2 was 95.7 ± 5.20%. Cardiopulmonary bypass, aortic cross‐clamp, postoperative mechanical ventilation, and hospitalization time were 101.7 ± 28.26 min, 60.9 ± 18.04 min, 16 h (8, 22), and 8 days (7, 11), respectively. The incidence of total postoperative adverse events, including low cardiac output syndrome, mechanical ventilation more than 3 days, postoperative hospitalization more than 2 weeks, postoperative reintubation, extracorporeal membrane oxygenation assistance, and death, was 13.1% ( n = 13). Low preoperative SPO2 ( p = .001, odds ratio [OR] = 0.834), GOS score ( p = .021, OR = 0.368), and cardiopulmonary bypass time ( p = .034, OR = 1.021) were risk factors for adverse events. Multivariate logistic regression analysis showed that low preoperative SPO2 ( p = .002, OR = 0.846) and GOS score ( p = .043, OR = 0.577) were independent risk factors for adverse events. The areas of SPO2 and GOS score under the ROC curve were 0.764 and 0.740, respectively. Conclusions: Low preoperative SPO2 and GOS score were predictors of adverse events after cone reconstruction, and SPO2 was more convenient and objective than the GOS score.